2014
DOI: 10.1007/s10461-014-0881-1
|View full text |Cite
|
Sign up to set email alerts
|

Usage and Acceptability of HIV Self-testing in Men who have Sex with Men in Hong Kong

Abstract: Whilst studies on over-the-counter HIV tests continue to accumulate after FDA's approval of OraQuick Advance in 2012, few have focused on men who have sex with men (MSM) in Asian cities. An internet survey was conducted on 1,122 MSM in Hong Kong, revealing a low usage (6.1 %) and acceptability rate (43.8 %) on self-testing despite its availability in the market. Hierarchical logistic regression models showed that having received relevant information and users' attitudes on self-testing were the determinants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 27 publications
1
34
1
Order By: Relevance
“…In the present study, the rate of HIVST uptake was 15.6%, which is lower than that in prior studies [12,20]. A decrease in HIVST uptake has also been observed in Hong Kong, likely because HIVST kits are not available for purchase over the counter [24]. In Chongqing, MSM have access to HIVST kits through e-commerce websites, hospitals, and Chongqing CDC offices.…”
Section: Discussioncontrasting
confidence: 80%
“…In the present study, the rate of HIVST uptake was 15.6%, which is lower than that in prior studies [12,20]. A decrease in HIVST uptake has also been observed in Hong Kong, likely because HIVST kits are not available for purchase over the counter [24]. In Chongqing, MSM have access to HIVST kits through e-commerce websites, hospitals, and Chongqing CDC offices.…”
Section: Discussioncontrasting
confidence: 80%
“…Globally, quality concerns about self-test kits sold over-the-counter have been expressed not only by self-test takers, but also by public health experts and policymakers [18]. In China, and specifically among MSM, several studies have found accuracy of HIV self-test kits to be a major concern [16, 17, 20, 28–30]. This lack of trust may be severely limiting the HIV self-testing uptake, and perhaps subsequent linkage to HIV care.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was adapted from that of a recent study by Wong and colleagues [20]. It was modified for the present study and then piloted among 110 MSM selected by convenience sampling methods from QQ, a popular Chinese instant messaging software service.…”
Section: Methodsmentioning
confidence: 99%
“…In general studies, which seek to understand how populations might accept HIVST (25) and Mexico (26) report that MSM find HIVST highly acceptable, with moderate acceptability observed in Hong Kong (27). In a recent cross-sectional study in England, HIVST was the second most preferred location for future HIV testing and tended to have greater popularity amongst MSM less likely to test at a frequency in line with national guidelines (28).…”
Section: Understanding Implementation Contexts: Values and Preferencesmentioning
confidence: 99%